Efektivitas Penggunaan Bahan Ajar Tematik untuk Meningkatkan Keterampilan Berpikir Kritis Mahasiswa Pendidikan Guru Sekolah Dasar - Ria Fajrin Rizqy Ana; Leny Suryaning Astutik (Jurnal Simki Postgraduate, 2025)
The problems that arise in terms of students are: most students have not been able to compile thematic model lesson plans, students have not been able to develop thematic learning models critically and creatively, students have not been able to determine the right theme as an umbrella for the various disciplines that will be taught. The aim of the research is to develop and test the effectiveness of teaching materials for Thematic Learning courses in improving students' critical thinking skills. The product trial subjects consisted of learning expert tests, subject matter experts, learning media experts, group tests, and field tests. The instruments used are validation sheets, questionnaires, tests of critical thinking skills. The teaching materials developed have proven to be quite effective in improving students' critical thinking skills. The results of the calculation of the N-gain test score 0.59 in the moderate category, 59.48% in the quite effective category, a significance value of 0.000 <0.05 there is a significant (real) difference in effectiveness between the use of developed teaching materials and existing teaching materials to improve skills critical thinking.